2013
DOI: 10.1111/jcal.12047
|View full text |Cite
|
Sign up to set email alerts
|

The role of scaffolding in CSCL in general and in specific environments

Abstract: This paper aims to analyse if virtual forums set up in an environment specifically designed to improve collaborative learning can effectively influence students' discourse quality and learning when compared with those forums set up in a general environment. Following a coding schema based upon the set of scaffolds offered in the Knowledge Forum environment, we have qualitatively analysed 60 forums and 1370 students from different subjects. The results show that there are very few elaborated and shared deep dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…One of the recent studies that explores the effects of a structured communication interface with a set of utterance patterns (eg, sentence openers, incomplete sentences) in a task‐based learning activity has indicated that the structured communication interface enhanced students' communicative competence and their collaborative productivity (Chiu, Wu, Hsieh, Cheng & Huang, ). According to Verdu and Sanuy (), scaffolds help students think about the type of contribution that they want to share in the online discussion platforms. The possible explanation for there being more reflective and elaborative discourse in the more scaffolded PBOAD platform might be that while sentence openers encourage students to think about their own contribution and consider the ideas that are sent by the other students, message labels may also help students focus more on their task and discussion intent.…”
Section: Discussionmentioning
confidence: 99%
“…One of the recent studies that explores the effects of a structured communication interface with a set of utterance patterns (eg, sentence openers, incomplete sentences) in a task‐based learning activity has indicated that the structured communication interface enhanced students' communicative competence and their collaborative productivity (Chiu, Wu, Hsieh, Cheng & Huang, ). According to Verdu and Sanuy (), scaffolds help students think about the type of contribution that they want to share in the online discussion platforms. The possible explanation for there being more reflective and elaborative discourse in the more scaffolded PBOAD platform might be that while sentence openers encourage students to think about their own contribution and consider the ideas that are sent by the other students, message labels may also help students focus more on their task and discussion intent.…”
Section: Discussionmentioning
confidence: 99%
“…Students tend to lack the competencies to take perspectives of others, support their opinions with evidence, make counterarguments, and integrate different perspectives, which may interfere with learning from collaborative argumentation ( Andriessen et al, 2003 ; Clark, D’Angelo, & Menekse, 2009 ; Nussbaum & Schraw, 2007 ). Teachers also have the concern that all students may not actively participate in collaborative argumentation because of low motivation or social presence ( Kwon, Liu, & Johnson, 2014 ; Verdú & Sanuy, 2014 ). To enhance collaborative argumentation, previous studies have investigated how to provide instructional support and feedback on participation, interaction patterns, and arguments ( Iandoli, Quinto, De Liddo, & Buckingham Shum, 2014 ; Jeong & Joung, 2007 ; Van Amelsvoort, Andriessen, & Kanselaar, 2007 ; Zheng, Xu, Li, & Su, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The research has focused on, for example, participation [7], learning outcomes [8], engagement [9], how learning is regulated [10,11], or how to better facilitate collaboration [12] and scaffold learning [13]. The research shows that online discussions are-and stay-task-oriented [8], that complex thought and high levels of knowledge building seem to be possible [14], and that interactions that involve differing opinions increase discussion, as well as critical thinking [15].…”
Section: Introductionmentioning
confidence: 99%